Overactive bladder (OAB) and its association with prostatic parameters - Khoo, E.M.; Tan, W.S.; Low, W.Y.; Ng, C.J.; Ho, E.L.M.; Tan, H.M. (Elsevier, 2011)
Background: Overactive bladder (OAB) is an idiopathic condition characterized by urgency with or without urge incontinence often associated with frequency or nocturia. In this study, we hypothesized that prostatic parameters might be responsible for symptoms seen in OAB patients.